Pengembangan Sistem Pergudangan Produk Teknik Berbasis Web Menggunakan Metode Waterfall (Studi Kasus PT. Fajria Fajar Asia) - Moch Ilham Nurmansyah; Achmad Arwan; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The warehouse management of Fajria Fajar Asia Ltd is everything that related to warehouse goods management of the Fajria Fajar Asia Ltd. Warehouse goods management that happen in Fajria Fajar Asia Ltd including procurement of goods, sales of goods, rental goods, and service goods. Problem is there less effective in the process of goods management of Fajria Fajar Asia Ltd because process of the goods management the goods management still carried out manually and conventionally along with Fajria Fajar Asia Ltd has three seperate warehouse buildings which make it difficult to coordinate one building with another. Because of the length of procedure starting from makes goods submission, check the completeness of goods data, approval from the financial administration, checking goods, until provide a goods report to the warehouse manager. Ineffective management of goods will waste time in the management of goods Fajria Fajar Asia Ltd. A system developed in this study is a goods management system to solve the problem of goods management at Fajria Fajar Asia Ltd. Waterfall is a system development used in this research. The stages carried out by the researcher in the study were problem identification, namely identifying problems in PT. Fajria Fajar Asia, literature study, needs engineering, design, implementation, testing, conclusions and suggestions. This system has been testing by performing unit testing, integration testing, and validation testing. Validation testing has 68 test case that produce valid status, unit testing has eight test case that produce valid status, integration testing has one test case that produce valid status.